2020
DOI: 10.3390/jcm9061969
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with Anticoagulation for Atrial Fibrillation: Report from the GLORIA-AF Phase III 1-Year Follow-up

Abstract: Background: We aimed to assess the extent to which drug persistence is better with non-vitamin K antagonist oral anticoagulants (NOACs) than vitamin K antagonists (VKAs) in atrial fibrillation (AF) patients and to estimate the difference in therapy persistence depending on NOAC dosing regimen (once daily (QD) vs. twice daily (BID)). Methods: Consecutive patients were followed for 1 year in phase III of the GLORIA-AF registry. Drug persistence was defined as the use of OAC without any discontinuation in >30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…A recent study based on 1-year follow-up phase III data from GLORIA-AF registry 43 found that drug persistence was higher with NOACs than with VKAs, without a significant difference in persistence when comparing NOAC dosing regimens (once daily vs. twice daily). 44 Nonetheless, in other studies, once daily NOACs were shown to increase adherence in comparison to twice daily NOACs. 14 , 27 , 45–48 …”
Section: Adherence and Persistence To Non-vitamin K Antagonist Oral A...mentioning
confidence: 90%
“…A recent study based on 1-year follow-up phase III data from GLORIA-AF registry 43 found that drug persistence was higher with NOACs than with VKAs, without a significant difference in persistence when comparing NOAC dosing regimens (once daily vs. twice daily). 44 Nonetheless, in other studies, once daily NOACs were shown to increase adherence in comparison to twice daily NOACs. 14 , 27 , 45–48 …”
Section: Adherence and Persistence To Non-vitamin K Antagonist Oral A...mentioning
confidence: 90%
“…The present study was conducted in 205,773 AF new users of DOACs in the Netherlands, Italy and Germany between 2011 and 2018. To our knowledge, it represents the largest study of its type, being at least one order of magnitude larger than previous studies [ 17 ]. Across the three European countries, adherence was significantly lower with BID vs QD regimens, with marginal differences in the Netherlands and Italy, but marked in Germany, where formal nonadherence to BID regimens was reached (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Expert opinion recommends a QD dosage regimen DOAC in patients who prefer a low pill burden [ 16 ]. Contemporary studies assessing treatment adherence by QD or BID DOAC regimens are few and limited in size [ 17 ]. The objective of the present study is to assess, in three large real-life samples of patients with AF, the adherence, persistence and switching patterns of QD vs BID regimens in three different European countries.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Was the data collected in a way that addressed the research issue? (6) Has the relationship between the researcher and participants been adequately considered? (7) Have ethical issues been taken into consideration?…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…As the disease progresses, patients with AF experience various heart symptoms and physical discomfort 5 . Moreover, AF also affects psychological well‐being, social connectedness and quality of life (QoL) 6 …”
Section: Introductionmentioning
confidence: 99%